Acute and chronic consequences of polidocanol foam injection in the lung in experimental animals. (December 2013) - Grandi, L; Grandi, R A; Tomasi, C D; Da Rocha, J L; Cardoso, V; Dal-Pizzol, F
Objective: To assess the presence of pulmonary embolism and inflammation after polidocanol foam injection into the peripheral veins of rabbits. Method: The animals were treated with polidocanol foam (1 or 3 mg/kg) or vehicle. Early (15 minutes) and late (30 days) animals were evaluated by perfusional lung scintigraphy and histopathological examination. Results: In the control group no alterations were found. After polidocanol foam injection it was observed that an important reduction of pulmonary perfusion in the early periods, was mainly in the left lung ( P < 0.001), with consequent embolism in the histological evaluation. In late periods it was observed that the presence of thrombus was with fibrin in small veins, compatible with chronic thrombus and the presence of chronic pulmonary inflammation. Conclusions: The injection of polidocanol foam in experimental animals can induce venous embolism and chronic inflammatory infiltration.